2020
DOI: 10.1002/14651858.cd003965.pub3
|View full text |Cite
|
Sign up to set email alerts
|

Immunosuppressive agents for treating IgA nephropathy

Abstract: Trusted evidence. Informed decisions. Better health.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
46
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(47 citation statements)
references
References 110 publications
0
46
1
Order By: Relevance
“…Concerning corticosteroids in adult IgAN, three main clinical studies [ 48 , 49 , 50 ] and one meta-analysis [ 51 ] are available. They showed that corticosteroids, after optimization supportive treatment (mainly RAAS blockers) and in addition to it, can decrease proteinuria and slow loss of kidney function, particularly in patients with persistent proteinuria more than 1 g/g and preserved renal function (eGFR > 50 mL/min/1.73 m 2 ).…”
Section: Treatmentmentioning
confidence: 99%
“…Concerning corticosteroids in adult IgAN, three main clinical studies [ 48 , 49 , 50 ] and one meta-analysis [ 51 ] are available. They showed that corticosteroids, after optimization supportive treatment (mainly RAAS blockers) and in addition to it, can decrease proteinuria and slow loss of kidney function, particularly in patients with persistent proteinuria more than 1 g/g and preserved renal function (eGFR > 50 mL/min/1.73 m 2 ).…”
Section: Treatmentmentioning
confidence: 99%
“…This condition has now become a global public health problem. IgA nephropathy (IgAN) and lupus nephritis (LN) is the most common primary and secondary glomerular diseases, respectively, and tend to affect young adults, with nearly 20% of patients progressing to ESRD after 10 years because of limited drug treatment options ( Mahajan et al, 2020 ; Natale et al, 2020 ). Although both diseases have complex and varied clinical manifestations, many overlaps have been noted.…”
Section: Introductionmentioning
confidence: 99%
“…Glomerular diseases are still common causes of end-stage renal disease (ESRD), a global health epidemic affecting more than 2 million people worldwide [1][2][3][4]. Many glomerular diseases are immunologically mediated disorders [1,[5][6][7][8], and immunosuppressive medications put glomerular disease patients at a high risk of various infections, such as pneumonia, Mycobacterium tuberculosis and hepatitis B virus reactivation, which contribute to the progression of disease per se and mortality [9][10][11][12][13][14]. In recent years, accumulating data have shown an increased rate of opportunistic infections in glomerular disease patients with longterm use of glucocorticoids and (or) immunosuppressive agents, especially in nephrotic syndrome, IgA nephropathy, lupus nephritis and vasculitis patients [14][15][16][17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%